Resistance mechanisms to osimertinib in EGFR-mutated advanced non-small-cell lung cancer: A multicentric retrospective French study. (November 2019) - Mehlman, Camille; Cadranel, Jacques; Rousseau-Bussac, Gaelle; Lacave, Roger; Pujals, Anaïs; Girard, Nicolas; Callens, Céline; Gounant, Valérie; Théou-Anton, Nathalie; Friard, Sylvie; Trédaniel, Jean; Blons, Hélène; et al.
Highlights: We report resistance mechanisms on osimertinib in lung cancer patients. We analyzed tissue and liquid biopsies collected at progression by NGS. C797S EGFR mutation and MET amplification were the most frequent mechanisms. Loss of T797M occurred in 68% of the cases. Patients treated with osimertinib in "real-life" experienced prolonged survival. Abstract: Objectives: The understanding of histo-molecular mechanisms associated with resistance to osimertinib is a critical step to define the optimal treatment strategy in advanced EGFR-mutated Non-Small-Cell-Lung-Cancer (NSCLC). Materials and methods: We performed a multicentric retrospective analysis on a cohort of consecutive patients treated with osimertinib for an advanced EGFR-mutated NSCLC and collected histo-molecular data from plasma and tumor samples at the time of progression. Next-generation sequencing (NGS) was performed for all samples. Best Overall Response Rate (ORR), Progression Free Survival (PFS), Overall Survival (OS) and data on treatment post-progression efficacy were also collected. Results: Two-hundred and twenty-six patients were included from 9 Academic French Hospitals between April 2015–October 2018. Osimertinib was given in second-line or more in 219 patients (97%). Best ORR was 52% and best central nervous system ORR was 56%. Median PFS and OS were 9.5 months (IQR 4.0-17.2) and 24 months (IQR 12.4-NR) respectively. At the time of analysis, 150 patients (66%) had tumor progression. Among them, 73 contributive samples (56 tumor biopsies) were available. The most frequent molecular alterations were C797S mutation (n = 9 (13%)) and MET amplification (n = 8 (11%)). Histologic transformation occurred in 5 patients (9% of tumor biopsies). In T790M + NSCLC, loss of T790 M occurred in 68% of cases. Median PFS and OS with treatment beyond progression were 6.0 months (IQR 2.0-10.4) and 15.1 months (IQR 6.7-NR) respectively and longer in case of osimertinib continuation beyond progression. Conclusion: We confirmed the efficacy of osimertinib in patients with advanced EGFR mutation positive NSCLC. At progression, the most frequent molecular alterations were MET amplification and C797S mutation.